Fiscal policy and international competitiveness: evidence from Ireland - Galstyan, Vahagn; Lane, Philip R. (Economic & Social Studies, 2009)
Our goal in this paper is to investigate the relation between government spending and the long-run behaviour of the Irish real exchange rate. We postulate that an increase in government consumption should be associated with real appreciation, while the impact of government investment is ambiguous. Empirically, we find that an increase in government consumption indeed appreciates the real exchange rate while an increase in government investment is associated with real depreciation. Accordingly, the level and composition of government spending matters for Irish external competitiveness.
Keywords: Fiscal policy; Competitiveness; Ireland; Real exchange rate